A guide to crisis intervention - Kanel, Kristi, 1958- (Stamford, CT : Cengage Learning, 2015)
Provides readers with the skills necessary to handle any crisis situation. This title utilizes the comprehensive ABC Model of Crisis Intervention, which can be used as effectively for day-to-day interactions as for emergency situations.
Includes bibliographical references and index.
Keywords: Crisis intervention (Mental health services); Crisis Intervention -- methods; Crisis intervention (Mental health services)